1987
DOI: 10.1203/00006450-198710000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Structure and Abundance of Cartilage Proteoglycans during Early Development of the Human Fetus

Abstract: ABSTRACT. Proteoglycan was isolated from the epiphyseal cartilage of the knee joint from human fetuses, ranging in age from 11 to 19 wk of gestation. The content of proteoglycan, per wet weight of cartilage, increased with gestational age, and structural changes were observed in the proteoglycan subunits, particularly with respect to hydrodynamic size and the position of sulfation of the chondroitin sulfate chains. While 6-sulfation remained fairly constant on about half the disaccharide residues during the ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
(41 reference statements)
2
9
0
Order By: Relevance
“…Ion exchange HPLC analyses of fluorotagged chondroitinase digestion products was done under conditions in which all internal ⌬disaccharides and nonreducing terminal monosaccharides and disaccharides are measured (26). The majority of the fluorescent products in the digests of human aggrecan represented the sulfated ⌬disaccharides (Table I), and in agreement with previous reports (3,6,7), the ratio of ⌬Di6S:⌬Di4S was about 0.75 in aggrecan CS from cartilages up to 1 year of age, but increased to a much higher level, ϳ25, in samples from individuals older than 15 years of age.…”
Section: Fluorescent Hplc Analyses Of Chondroitinase Digests Fromsupporting
confidence: 87%
“…Ion exchange HPLC analyses of fluorotagged chondroitinase digestion products was done under conditions in which all internal ⌬disaccharides and nonreducing terminal monosaccharides and disaccharides are measured (26). The majority of the fluorescent products in the digests of human aggrecan represented the sulfated ⌬disaccharides (Table I), and in agreement with previous reports (3,6,7), the ratio of ⌬Di6S:⌬Di4S was about 0.75 in aggrecan CS from cartilages up to 1 year of age, but increased to a much higher level, ϳ25, in samples from individuals older than 15 years of age.…”
Section: Fluorescent Hplc Analyses Of Chondroitinase Digests Fromsupporting
confidence: 87%
“…In adult hyaline cartilage, sulfated GAG content, on a weight basis, is more than an order of magnitude greater than the HA content. During development, however, it has been shown that non-sulfated disaccharide content starts higher than 4-sulfated GAG but decreases significantly with age [39]. Collectively, it suggests that the ECM formed is relatively ‘young’ compared to adult articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…33,39 In the fetus, much of the N-acetylgalactosamine may be nonsulfated. 42 In contrast to chondroitin sulfate, keratan sulfate chain length increases during juvenile development. 5,46 Although the aggrecan core protein shows structural variation attributable to alternative splicing, this does not seem to be age-related.…”
Section: Number 391s October 2001mentioning
confidence: 98%